Evaluating Environmental Service of Trisula Waterfall as Nature-based Tourism Attraction in Bromo Tengger Semeru National Park - Hamdani Dwi Prasetyo; Luchman Hakim; Catur Retnaningdyah (Program Pascasarjana, 2017)
Tourism activity in Trisula waterfall (locally called Coban Trisula) is growing significantly. The environmental management is important to perform the sustainable use of waterfall as tourism attraction. The aim of the research is to identify the ecosystem services of Trisula waterfall. In this study, three indices were calculated, namely Environmental Services Index, Hemeroby Index, and Naturalness index. This study found that the use of lands and natural resources in Trisula waterfall was low compared the upper and lower area. Lower and upper area was used for intensive agriculture and daily needs by local community. Those activities were influencing the environmental services of Trisula waterfall. Management towards sustainable use of Coban Trisula area was required. It is also important and should be able to promote security and satisfaction aspects for tourist. Anthropogenic activities such as plantation activities should be controlled by a persuasive approach to minimize disruption to the ecosystem. There are needs for environmental management to ensure the sustainability use of waterfall resources and its surrounding area.Keywords: sustainable tourism, waterfall management, water conservation.